Processing technology of carbon nanotube composite conductive paste
By using carbon nanotubes and graphene combined with dispersant and modified polyurethane emulsion in conductive pastes, the dispersion and water resistance of conductive pastes are solved, the conductive properties and mechanical strength are improved, and the more Good bonding and conductivity.
Patent Information
- Application Number
- CN202411350774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
The existing conductive paste containing carbon nanotubes has problems such as poor dispersion, poor water resistance, poor conductivity and mechanical strength, which leads to a reduced adhesive capacity after film formation and poor conductivity.
Carbon nanotubes and graphene as main raw materials are combined with dispersants and modified polyurethane emulsion and N-methylpyrrolidone for compounding. The dispersion of carbon nanotubes is improved through ultrasonic crushing and sanding treatment, and silane modified polyurethane resin is used. Materials such as glass fiber improve conductivity and mechanical strength.
The dispersion and conductivity of carbon nanotubes are significantly improved, the mechanical strength and toughness after film formation are enhanced, and the water resistance and bonding ability of conductive pastes are improved.
Smart Images

Figure BDA0005062300250000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to a processing technology of carbon nanotube composite conductive paste. Background Art
[0002] Conductive paste is one of the core materials of lithium battery conductive agent, usually composed of conductive filler and polymer binder and other raw materials, wherein the conductive filler includes carbon materials such as carbon nanotubes, graphene, graphite and conductive carbon black, and the polymer binder includes polymer materials such as polyester, polyurethane and epoxy resin. Among them, waterborne polyurethane has excellent safety, environmental protection, chemical resistance and oil resistance, and has high mechanical properties and good flexibility after film formation, and is usually selected as a polymer binder for matching with graphene. However, waterborne polyurethane contains more hydrophilic groups, which makes the water resistance of the conductive paste containing waterborne polyurethane poor, resulting in poor water resistance after film formation, and the bonding ability is significantly reduced after multiple washings, and it is very easy to fall off from the flexible circuit board. At the same time, the dispersion of carbon nanotubes is not good, and it is easy to agglomerate. The compatibility between carbon nanotubes and waterborne polyurethane is also not good, which makes the conductive performance and mechanical strength of the conductive paste after film formation not ideal. Therefore, there is a lot of room for improvement in this direction. Summary of the invention
[0003] In view of the problems of current conductive pastes containing carbon nanotubes, the present invention aims to provide a processing technology for carbon nanotube composite conductive paste, which can improve the dispersibility of carbon nanotubes and make the paste have better conductive properties and mechanical strength after film formation.
[0004] The purpose of the present invention is to provide a processing technology for carbon nanotube composite conductive paste:
[0005] The processing technology uses carbon nanotubes and graphene as main raw materials, and is compounded with dispersants, modified polyurethane emulsions, and N-methylpyrrolidone to complete the processing of the conductive paste.
[0006] Furthermore, the processing technology comprises the following steps:
[0007] (1) Taking, by weight, 80 to 100 parts of carbon nanotubes, 30 to 50 parts of graphene, 2 to 7 parts of dispersant, 130 to 160 parts of modified polyurethane emulsion, and 1500 to 4000 parts of N-methylpyrrolidone;
[0008] (2) firstly taking carbon nanotubes, graphene, modified polyurethane emulsion, and N-methylpyrrolidone, mixing and stirring, and then ultrasonically crushing, to obtain a composite carbon nanotube dispersion;
[0009] (3) adding a dispersant to the composite carbon nanotube dispersion to mix the mixture, sand grinding the mixture with a sand mill, and then performing ultrasonic dispersion treatment to obtain a carbon nanotube composite conductive slurry.
[0010] Furthermore, the ultrasonic crushing treatment in step (2) is carried out at a power of 300 to 500 W for 10 to 30 minutes, and the ultrasonic dispersion treatment in step (3) is carried out at a power of 100 to 300 W for 20 to 40 minutes. First, ultrasonic crushing treatment is performed to cause instantaneous cracking, shearing and fragmentation inside the material, and the main material is activated with a large specific surface area, which is convenient for the preparation of the conductive slurry; the subsequent ultrasonic dispersion treatment is used for dynamic dispersion, uniform mixing, and stable slurry properties.
[0011] Furthermore, the dispersant is a mixture of polyester wax and ethylene bisstearamide in a mass ratio of 3 to 6:1.
[0012] Furthermore, the carbon nanotubes have a diameter of 5 to 50 nm, a length of less than 10 μm, and a specific surface area of 50 to 350 m 2 / g.
[0013] Further, the preparation of the modified polyurethane emulsion:
[0014] By mass, 60 to 80 parts of silane-modified polyurethane resin, 12 to 20 parts of polypropylene carbonate diol, 2 to 5 parts of fiber material, and 1 to 3 parts of epoxy soybean oil are mixed, heated to 40 to 60° C., stirred, and maintained for 30 to 60 minutes to obtain a modified polyurethane emulsion.
[0015] Furthermore, the fiber material is a mixture of glass fiber and polypropylene fiber in a mass ratio of 3 to 5:1, and the particle size is controlled to be 0.1 to 0.3 mm.
[0016] Compared with the prior art, the advantages of the present invention are:
[0017] (1) The ethylene bisstearamide in the dispersant used in the present invention contains two amide groups -C-NH- in its molecular structure, which can provide good antistatic properties in the slurry system. When used in combination with the long-chain dispersant polyester wax, a significant synergistic effect can be achieved, which can improve the dispersibility of carbon nanotubes and graphene in the slurry system;
[0018] (2) The present invention uses silane-modified polyurethane resin as the main body of the modified polyurethane emulsion, wherein the molecular structure of the silane-modified polyurethane resin contains a large number of carbonate groups and ether bonds. The carbonate groups with greater polarity can form high-density hydrogen bonds with other polar groups, thereby improving the cohesive energy of the slurry system and ensuring the conductive performance of the slurry system. At the same time, by increasing the intermolecular force, a greater external force is required for relative displacement between molecules, thereby improving the vibration resistance and mechanical properties; the ether bonds and silane groups in the silane-modified polyurethane resin improve its compatibility in the slurry system, and the introduction of silane chain segments increases flexibility, improves toughness, and improves overall strength; glass fiber and polypropylene fiber with very low hygroscopicity are used as fillers to play a reinforcing role, further improving the overall mechanical strength and the insulating properties of the fiber material, and facilitating the construction of conductive channels and improving conductive performance. DETAILED DESCRIPTION
[0019] The following is a specific embodiment of the processing technology of a carbon nanotube composite conductive paste of the present invention. It is necessary to point out that the following examples are only used to explain the present invention in more detail, rather than to narrow the scope of protection of the present invention. After reading the present invention, the improvements and adjustments made by professionals in this technical field without departing from the concept of the present invention are within the scope of protection required by the present invention.
[0020] A processing technology for carbon nanotube composite conductive paste specifically comprises the following steps:
[0021] (1) Taking, by weight, 80 to 100 parts of carbon nanotubes, 30 to 50 parts of graphene, 2 to 7 parts of dispersant, 130 to 160 parts of modified polyurethane emulsion, and 1500 to 4000 parts of N-methylpyrrolidone;
[0022] (2) firstly taking carbon nanotubes, graphene, modified polyurethane emulsion, and N-methylpyrrolidone, mixing and stirring for 2 to 3 hours, and then treating with an ultrasonic cell crusher at a power of 300 to 500 W for 10 to 30 minutes to obtain a composite carbon nanotube dispersion;
[0023] (3) Adding a dispersant to the composite carbon nanotube dispersion and mixing the mixture, sand milling the mixture for 1 to 2 hours, and treating the mixture at a power of 100 to 300 W for 20 to 40 minutes to obtain a carbon nanotube composite conductive slurry.
[0024] The dispersant is a mixture of polyester wax and ethylene bisstearic acid amide in a mass ratio of 3 to 6:1.
[0025] The diameter of carbon nanotubes is 5-50nm, the length is less than 10μm, and the specific surface area is 50-350m 2 / g.
[0026] Among them, the preparation of modified polyurethane emulsion: by mass, take 60-80 parts of silane modified polyurethane resin, 12-20 parts of polypropylene carbonate diol, 2-5 parts of fiber material, and 1-3 parts of epoxy soybean oil, mix them, heat them to 40-60°C, stir them evenly, and keep them for 30-60 minutes to obtain modified polyurethane emulsion.
[0027] The fiber material is a mixture of glass fiber and polypropylene fiber in a mass ratio of 3 to 5:1, and the particle size is controlled to be 0.1 to 0.3 mm.
[0028] Example 1
[0029] A processing technology for carbon nanotube composite conductive paste specifically comprises the following steps:
[0030] (1) Taking, by weight, 90 parts of carbon nanotubes, 40 parts of graphene, 4 parts of dispersant, 145 parts of modified polyurethane emulsion, and 1700 parts of N-methylpyrrolidone;
[0031] (2) First, carbon nanotubes, graphene, modified polyurethane emulsion, and N-methylpyrrolidone were mixed and stirred for 2.5 hours, and then treated with an ultrasonic cell crusher at a power of 400 W for 20 minutes to obtain a composite carbon nanotube dispersion;
[0032] (3) Adding a dispersant to the composite carbon nanotube dispersion and mixing the mixture, stirring the mixture with a magnetic force for 1 hour, and treating the mixture at a power of 200 W for 30 minutes to obtain a carbon nanotube composite conductive slurry.
[0033] The dispersant is a mixture of polyester wax and ethylene bisstearamide in a mass ratio of 4:1.
[0034] The diameter of carbon nanotubes is 5-50nm, the length is less than 10μm, and the specific surface area is 50-350m 2 / g.
[0035] Among them, the preparation of modified polyurethane emulsion: by mass, take 70 parts of silane modified polyurethane resin, 15 parts of polypropylene carbonate diol, 3 parts of fiber material, and 2 parts of epoxy soybean oil, mix them, heat them to 50°C, stir them evenly, and keep them for 50 minutes to obtain modified polyurethane emulsion.
[0036] The fiber material is a mixture of glass fiber and polypropylene fiber in a mass ratio of 4:1, and the particle size is controlled to be 0.1-0.3 mm.
[0037] Example 2
[0038] A processing technology for carbon nanotube composite conductive paste specifically comprises the following steps:
[0039] (1) Taking 80 parts of carbon nanotubes, 30 parts of graphene, 2 parts of dispersant, 130 parts of modified polyurethane emulsion, and 1800 parts of N-methylpyrrolidone by weight;
[0040] (2) First, carbon nanotubes, graphene, modified polyurethane emulsion, and N-methylpyrrolidone were mixed and stirred for 2.5 hours, and then treated with an ultrasonic cell crusher at a power of 400 W for 20 minutes to obtain a composite carbon nanotube dispersion;
[0041] (3) Adding a dispersant to the composite carbon nanotube dispersion and mixing the mixture, stirring the mixture with a magnetic force for 1 hour, and treating the mixture at a power of 200 W for 30 minutes to obtain a carbon nanotube composite conductive slurry.
[0042] The dispersant is a mixture of polyester wax and ethylene bisstearamide in a mass ratio of 4:1.
[0043] The diameter of carbon nanotubes is 5-50nm, the length is less than 10μm, and the specific surface area is 50-350m 2 / g.
[0044] Among them, the preparation of modified polyurethane emulsion: by mass, take 70 parts of silane modified polyurethane resin, 15 parts of polypropylene carbonate diol, 3 parts of fiber material, and 2 parts of epoxy soybean oil, mix them, heat them to 50°C, stir them evenly, and keep them for 50 minutes to obtain modified polyurethane emulsion.
[0045] The fiber material is a mixture of glass fiber and polypropylene fiber in a mass ratio of 4:1, and the particle size is controlled to be 0.1-0.3 mm.
[0046] Example 3
[0047] A processing technology for carbon nanotube composite conductive paste specifically comprises the following steps:
[0048] (1) Taking, by weight, 100 parts of carbon nanotubes, 50 parts of graphene, 7 parts of dispersant, 160 parts of modified polyurethane emulsion, and 4000 parts of N-methylpyrrolidone;
[0049] (2) First, carbon nanotubes, graphene, modified polyurethane emulsion, and N-methylpyrrolidone were mixed and stirred for 2.5 hours, and then treated with an ultrasonic cell crusher at a power of 400 W for 20 minutes to obtain a composite carbon nanotube dispersion;
[0050] (3) Adding a dispersant to the composite carbon nanotube dispersion and mixing the mixture, stirring the mixture with a magnetic force for 1 hour, and treating the mixture at a power of 200 W for 30 minutes to obtain a carbon nanotube composite conductive slurry.
[0051] The dispersant is a mixture of polyester wax and ethylene bisstearamide in a mass ratio of 4:1.
[0052] The diameter of carbon nanotubes is 5-50nm, the length is less than 10μm, and the specific surface area is 50-350m 2 / g.
[0053] Among them, the preparation of modified polyurethane emulsion: by mass, take 70 parts of silane modified polyurethane resin, 15 parts of polypropylene carbonate diol, 3 parts of fiber material, and 2 parts of epoxy soybean oil, mix them, heat them to 50°C, stir them evenly, and keep them for 50 minutes to obtain modified polyurethane emulsion.
[0054] The fiber material is a mixture of glass fiber and polypropylene fiber in a mass ratio of 4:1, and the particle size is controlled to be 0.1-0.3 mm.
[0055] Comparative Example 1: The same as Example 2, except that the dispersant was omitted.
[0056] Comparative Example 2: The method is basically the same as Example 2, except that the modified polyurethane emulsion is omitted.
[0057] Comparative Example 3: The same as Example 2, except that the ultrasonic crushing and ultrasonic dispersion treatments in steps (2) and (3) were replaced by magnetic stirring at 500 r / min.
[0058] Resistivity test: The conductive paste samples prepared in Examples 1 to 3 and the conductive paste samples in Comparative Examples 1 to 3 were homogenized and then coated on a 30 cm*20 cm Pl film substrate. The coated substrate was placed in an oven for drying and then tested. 5 cm was cut off at each end of the substrate and tested with a four-probe tester. Nine points were taken in the middle according to a nine-square grid and tested and recorded, and the average value was calculated. See Table 1 for specific test results.
[0059] Button charge and discharge test: The conductive slurry samples prepared in Examples 1 to 3 and the conductive slurry samples in Comparative Examples 1 to 3 were used to prepare batteries, the conductive slurry was coated on graphite, and dried in a vacuum oven at 120°C for 10 hours to form a negative electrode sheet with a diameter of 12 mm. Lithium iron phosphate was used as the counter electrode and assembled into CR2025 button batteries in a glove box. The diaphragm was Celgard2300, and the electrolyte was 1 mol / L LiPF6 / EC+DEC (the volume ratio of EC and DEC was 1:1).
[0060] The button cell was used to measure the charging capacity at 0.1C, 0.3C, 0.5C, 1C and 1.5C, and the temperature rise data of the battery was measured at 1C. The specific test results are shown in Table 1.
[0061] Table 1. Statistical table of various parameters of conductive paste samples of embodiments and comparative examples
[0062]
[0063] It can be seen from Table 1 that the resistivity of the conductive pastes prepared in Examples 1 to 3 is lower than that of Comparative Examples 1 to 3, and the tested charging capacities of Examples 1 to 3 are greater than those of Comparative Examples 1 to 3. It can be seen that some key steps of the present invention play a role. First, the dispersant is omitted in Comparative Example 1, which may be due to dispersibility issues, resulting in a certain degree of increase in resistivity and a decrease in charging capacity. The modified polyurethane emulsion is omitted in Comparative Example 2, which significantly increases the resistivity and has a significant negative effect. Furthermore, the ultrasonic crushing treatment and ultrasonic dispersion treatment in steps (2) and (3) are replaced by magnetic stirring at 500 r / min, and the resistivity and charging capacity are relatively reduced, but the magnitude is relatively smaller than that of Comparative Examples 1 and 2, which shows the importance of this step in the present application. Although it seems to be a routine operation, it can achieve a certain optimization effect and is an optimization point that can be considered.
[0064] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A process for processing carbon nanotube composite conductive paste, characterized in that: The processing technology uses carbon nanotubes and graphene as main raw materials, and combines them with dispersants, modified polyurethane emulsions and N-methylpyrrolidone for compounding to complete the processing of conductive paste.
2. The processing technology of carbon nanotube composite conductive paste according to claim 1, characterized in that: The processing technology includes the following steps: (1) Taking, by weight, 80 to 100 parts of carbon nanotubes, 30 to 50 parts of graphene, 2 to 7 parts of dispersant, 130 to 160 parts of modified polyurethane emulsion, and 1500 to 4000 parts of N-methylpyrrolidone; (2) firstly mixing carbon nanotubes, graphene, modified polyurethane emulsion and N-methylpyrrolidone, and then ultrasonically crushing them to obtain a composite carbon nanotube dispersion; (3) adding a dispersant to the composite carbon nanotube dispersion to mix the mixture, sand grinding the mixture with a sand mill, and then performing ultrasonic dispersion treatment to obtain a carbon nanotube composite conductive slurry.
3. The processing technology of carbon nanotube composite conductive paste according to claim 2, characterized in that: The ultrasonic crushing treatment in step (2) is carried out at a power of 300 to 500 W for 10 to 30 minutes, and the ultrasonic dispersion treatment in step (3) is carried out at a power of 100 to 300 W for 20 to 40 minutes.
4. The processing technology of carbon nanotube composite conductive paste according to claim 1 or 2, characterized in that: The dispersant is a mixture of polyester wax and ethylene bisstearic acid amide in a mass ratio of 3 to 6:
1.
5. The processing technology of carbon nanotube composite conductive paste according to claim 1 or 2, characterized in that: The carbon nanotube has a diameter of 5 to 50 nm, a length of less than 10 μm, and a specific surface area of 50 to 350 m 2 / g.
6. The processing technology of carbon nanotube composite conductive paste according to claim 1 or 2, characterized in that: Preparation of the modified polyurethane emulsion: By mass, 60 to 80 parts of silane-modified polyurethane resin, 12 to 20 parts of polypropylene carbonate diol, 2 to 5 parts of fiber material, and 1 to 3 parts of epoxy soybean oil are mixed, heated to 40 to 60° C., stirred, and maintained for 30 to 60 minutes to obtain a modified polyurethane emulsion.
7. The processing technology of carbon nanotube composite conductive paste according to claim 6, characterized in that: The fiber material is a mixture of glass fiber and polypropylene fiber in a mass ratio of 3 to 5:1, and the particle size is controlled to be 0.1 to 0.3 mm.